Novel Approaches to Global Benchmarking of Risk-Adjusted Surgical Outcomes - Spence, Richard Trafford (Department of Surgery, 2019)
Background Despite the existence of multiple validated risk-assessment and quality benchmarking tools in surgery, their utility outside of High Income Countries is limited. We sought to derive, validate and apply a scoring system that is both 1) feasible, and 2) reliably predicts mortality in a Middle Income Country (MIC) context.